Hodnocení finanční situace podniku a návrhy na její zlepšení - Dvořák, David (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalářská práce hodnotí finanční situaci podniku Etiflex, s.r.o. v období 2007 – 2011 pomocí vybraných ukazatelů finanční analýzy. Obsahuje také návrhy řešení zjištěných problémů, které mají vést ke zlepšení finanční situace podniku v budoucnosti.

This bachelor`s thesis analyses the financial situation of company Etiflex, s.r.o. within the years 2007 – 2011, by selected indicators of the financial analysis. It includes also proposals of solutions for identified problems which should result in improvement of the financial situation of the company in the following years.
Evaluation of the Financial Situation of a Company and Proposals for its Improvement
Keywords: Finanční analýza; rozvaha; výkaz zisku a ztráty; likvidita; rentabilita; zadluženost; poměrové ukazatele; vertikální a horizontální analýza.; Financial analysis; balance-sheet; profit and loss account; liquidity; profitability; indebtedness; ratio indicators; vertical and horizontal analysis.